PHYSICOCHEMICAL PROFILE AND SENSORY EVALUATION OF CAKES WITH FLAXSEED AND YACON FLOUR ASSOCIATED TO SWEETENERS - ALMEIDA, NATÁLIA TODESCHINI; SCHMIDT, HELENA; OLIVEIRA, VIVIAVI RUFFO DE (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2014)
The objective of this study was to evaluate the chemical, physical and sensory characteristics of cakes made with yacon and flaxseed flour as an alternative for patients with Diabetes. Four cakes were prepared: standard cake (CS) – yacon flour, flaxseed flour and sugar; cake A (CA) – yacon flour and flaxseed flour; cake B (CB) – yacon flour, flaxseed flour and sucralose and acesulfame-k; cake C (CC) – yacon flour, flaxseed flour and stevia. Moisture, carbohydrates, proteins, lipids, dietary fiber, ash and energy value of the products were evaluated. For the physical analysis were determined before and after cooking weight and height, and thermal factor. For sensory analysis, 40 untrained people evaluated appearance, color, texture, flavor, overall acceptability and purchase intention. All the cakes had great fibers intake. The cake with more calories and carbohydrate content was CS. This cake also had a higher weight before and after cooking. In sensory evaluation, the cakes did not showed significant differences in appearance and color. In flavor attributes, overall acceptance and in intention to purchase, CS and CB were better accepted. Thus, it can be concluded that the cake with yacon and flaxseed associated to sucralose and acesulfame-k is a good alternative for patients with Diabetes mellitus due to functional properties and good fiber content.